Analisis Kompetensi Sumber Daya Manusia Pangkalan Korps Marinir Jakarta (Lanmar Jakarta) Guna Mendukung Tugas Korps Marinir - Pristianto, Teguh (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
This research aims to analyze the competency of human resources at the Jakarta Marine Corps Base (LANMAR Jakarta) to support the duties of the Marine Corps. This research uses a qualitative approach to gain an in-depth understanding of the competencies possessed by human resources at LANMAR Jakarta as well as the factors that influence their competencies. The research method used was in-depth interviews and observations of LANMAR Jakarta personnel. Data obtained from interviews and observations were analyzed using a thematic approach. Data were analyzed inductively by identifying main themes that emerged from interviews and observations. The research results show that human resources at LANMAR Jakarta have quite good competence in supporting the duties of the Marine Corps. Competencies discovered include tactical ability, leadership, technical skills, and military knowledge. However, there are several factors that influence the competency of human resources at LANMAR Jakarta, including access to training and development, recognition of work achievements, and the use of technology to support operational activities. The conclusion of this research is that the competency of human resources at LANMAR Jakarta is quite good in supporting the duties of the Marine Corps. However, there are several areas that need attention to improve competence, such as developing technical skills in the fields of communications, information technology and logistics management. This research's recommendations include increasing access to training and development, implementing clear recognition and reward systems, better use of information technology, and increasing collaboration with educational institutions and other institutions.